Impact of a tobacco smoke on a metabolism of an organ culture of bovine lenses and potential protection by antioxidants - Bormusov, E.; Reznick, A.Z. (Актуальні проблеми транспортної медицини, 2013)
Smoke from cigarette smoking (CS) has been proposed to be a major environmental risk factor for a variety of human diseases and was implicated also in cataract, an eye lens pacification, which is a major cause of blindness. We have undertaken a study to investigate the effect of smoke on the physiological integrity and metabolism of organ cultured lenses. Lenses in organ culture are metabolically active and have functional defense systems, thus they pr ovide an appropriate model for studying the effects of smoke. Also possible protective action of N-acetyl L-cysteine (NAC) which is a precursor of glutathione and the iron chelator Deferoxamine (DFO), was estimated as potential protective agents against cataract.